24+9x-12x=3x-4x

Simple and best practice solution for 24+9x-12x=3x-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24+9x-12x=3x-4x equation:


Simplifying
24 + 9x + -12x = 3x + -4x

Combine like terms: 9x + -12x = -3x
24 + -3x = 3x + -4x

Combine like terms: 3x + -4x = -1x
24 + -3x = -1x

Solving
24 + -3x = -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
24 + -3x + x = -1x + x

Combine like terms: -3x + x = -2x
24 + -2x = -1x + x

Combine like terms: -1x + x = 0
24 + -2x = 0

Add '-24' to each side of the equation.
24 + -24 + -2x = 0 + -24

Combine like terms: 24 + -24 = 0
0 + -2x = 0 + -24
-2x = 0 + -24

Combine like terms: 0 + -24 = -24
-2x = -24

Divide each side by '-2'.
x = 12

Simplifying
x = 12

See similar equations:

| 1.5x=2(x-15) | | -0.6+(2.5)= | | 24p+16=32p-48 | | 9x^2-51x=168 | | -8+1=-14+7 | | (2x-2)2-10(2x-2)+21=0 | | X-1=11+5x | | 2y^3-2y^2-6y-10=0 | | 15x-7[x+2]=5x-2 | | X-.33x=25000 | | -68-(-25)= | | N+1=3n+9 | | (xy)dx+(x+1)dy=0 | | 0.95x+0.05(2-x)=0.10(163) | | 4z^2-4x=24 | | 12 = k2 + 10 | | 72x^2-8x+9=0 | | 3.5+(-7.5)= | | -1-6p=6-7p | | n-9-9n=1-7n | | 7=2g+3 | | 6+6n=-4(2-5n) | | 3.5+(7.5)= | | 28-6x=49-9x | | (X+1)=x | | 14y+41=139 | | 0.33333333333(21-3a)=6-a | | 3x+2x-11=84 | | 6x+0.4=6.4 | | -2x-18=-(1-2x)+4x | | 4(a+2)=14-2(3-a) | | 4n=5-5n |

Equations solver categories